Análise das mudanças de uso e ocupação da terra na região hidrográfica dos rios Cuiabá e São Lourenço entre 2002 e 2014 e modelagens preditivas - Muñoz Vásquez, Sebastián Isaías Jorge (2018)
Understanding the use and occupation of land, its spatio-temporal patterns in the territory and its prediction is of crucial importance to subsidize sustainable development and environmental, economic, cultural, etc. management. In this context, the present study aims to analyze the changes in land use and occupation in the Cuiabá and São Lourenço Rivers Basin between 2002 and 2014. Exploratory analyzes show significant dynamics, but without clear causal relationships with the possible driver’s processes. Most of the areas of Planalto with high agricultural aptitude have been deforested for more than 30 years, extrapolating in some areas the limits of the current environmental legislation. Deforestation currently occurs in Cerrado areas on soils of low agricultural potential in the Cuiabana Depression, with the installation of eucalyptus plantations and the generation of anthropic areas, which are soon changed to cultivation and pasture, in shallow soils developed on pre-Cambrian formations. and modifying their agricultural aptitude through agro-technological innovation, which bring an excessive level of changes in land use and occupation.